2020
DOI: 10.1002/onco.13604
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Lockdown: Impact of the COVID-19 Pandemic on Patients with Cancer

Abstract: The lockdown measures of the ongoing COVID-19 pandemic have disengaged patients with cancer from formal health care settings, leading to an increased use of social media platforms to address unmet needs and expectations. Although remote health technologies have addressed some of the medical needs, the emotional and mental well-being of these patients remain underexplored and underreported. We used a validated artificial intelligence framework to conduct a comprehensive real-time analysis of two data sets of 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 10 publications
4
97
0
1
Order By: Relevance
“…A study on head and neck cancer patients from Germany revealed that 40% were anxious regarding their disease but also in regard to the psychological and physical consequences of the pandemic. Social isolation (prohibition of visits) was reported to be a main problem (58.5%) [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…A study on head and neck cancer patients from Germany revealed that 40% were anxious regarding their disease but also in regard to the psychological and physical consequences of the pandemic. Social isolation (prohibition of visits) was reported to be a main problem (58.5%) [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine long hailed as the future of healthcare did not truly become realized until 2020. Researchers even used social media and the Patient-Reported Information Multidimensional Exploration (PRIME) framework to track the well-being of cancer patients during the lockdown [14] . They identified areas of anxiety in large populations and were able to plan and provide for interventions of emotional support [14] .…”
Section: Diagnosis: Social Media and Radiomicsmentioning
confidence: 99%
“…Research indicates that during the pandemic patients have sought informational and emotional support on social media (SM) and Twitter in particular [13]. This should not come as a surprise: SM platforms are increasingly recognized as promising tools in the delivery of health information and behavioral interventions to the public, especially to AYA with cancer given the extensive use of SM among this age cohort [14,15].…”
Section: Introductionmentioning
confidence: 99%